Obinutuzumab combined with lenalidomide for relapsed or refractory follicular B-cell lymphoma (GALEN): a multicentre, single-arm, phase 2 study. Issue 8 (August 2019) - Morschhauser, Franck; Le Gouill, Steven; Feugier, Pierre; Bailly, Sarah; Nicolas-Virelizier, Emmanuelle; Bijou, Fontanet; Salles, Gilles A; Tilly, Hervé; Fruchart, Christophe; Van Eygen, Koen; Snauwaert, Sylvia; Bonnet, Christophe; et al.
Summary: Background: Lenalidomide plus rituximab is approved to treat patients with relapsed or refractory follicular lymphoma. Obinutuzumab has been shown to enhance antibody-dependent cellular cytotoxicity, phagocytosis, and direct B-cell killing better than rituximab. Our aim was to determine the activity and safety of lenalidomide plus obinutuzumab in previously treated patients with relapsed or refractory follicular lymphoma. Methods: In this multicentre, single-arm, phase 2 study, patients were enrolled from 24 Lymphoma Academic Research Organisation centres in France. Eligible patients (age ≥18 years) had histologically confirmed CD20-positive relapsed or refractory follicular lymphoma of WHO grade 1, 2, or 3a; an ECOG performance status of 0–2; and received at least one previous rituximab-containing therapy. Patients received oral lenalidomide (20 mg) plus intravenously infused obinutuzumab as induction therapy (1000 mg; six 28-day cycles), 1-year maintenance with lenalidomide (10 mg; 12 28-day cycles; days 2–22) plus obinutuzumab (1000 mg; alternate cycles), and 1-year maintenance with obinutuzumab (1000 mg; six 56-day cycles; day 1). The primary endpoint was the proportion of patients who achieved an overall response at induction end as per investigator assessment using the 1999 international working group criteria. The secondary endpoints were event-free survival, progression-free survival, overall survival, and safety. Analyses were per-protocol; the efficacy population included all patients who received at least one dose of both obinutuzumab and lenalidomide, and the safety population included all patients who received one dose of either investigational drug. The study is registered with ClinicalTrials.gov, number NCT01582776, and is ongoing but closed to accrual. Findings: Between June 11, 2014, and Dec 18, 2015, 89 patients were recruited and 86 patients were evaluable for efficacy and 88 for safety. Median follow-up was 2·6 years (IQR 2·2–2·8). 68 (79%) of 86 evaluable patients (95% CI 69–87) achieved an overall response at induction end, meeting the prespecified primary endpoint. At 2 years, event-free survival was 62% (95% CI 51–72), progression-free survival 65% (95% CI 54–74), duration of response 70% (95% CI 57–79), and overall survival 87% (95% CI 78–93). Complete response was achieved by 33 (38%, 95% CI 28–50) of 86 patients at induction end, and the proportion of patients achieving a best overall response was 70 (81%, 95% CI 72–89) and 72 (84%, 74–91) of 86 patients during induction and treatment, respectively. The most common adverse events were asthenia (n=54, 61%), neutropenia (n=38, 43%), bronchitis (n=36, 41%), diarrhoea (n=35, 40%), and muscle spasms (n=34, 39%). Neutropenia was the most common toxicity of grade 3 or more; four (5%) patients had febrile neutropenia. 57 serious adverse events were reported in 30 (34%) of 88 patients. The most common serious adverse events were basal cell carcinoma (n=5, 6%), febrile neutropenia (n=4, 5%), and infusion-related reaction (n=3, 3%). One patient died due to treatment-related febrile neutropenia. Interpretation: Our data shows that lenalidomide plus obinutuzumab is active in previously treated patients with relapsed or refractory follicular lymphoma, including those with early relapse, and has a manageable safety profile. Randomised trials of new immunomodulatory regimens, such as GALEN or using GALEN as a backbone, versus lenalidomide plus rituximab, are warranted. Funding: Lymphoma Academic Research Organisation, and Celgene and Roche